Latent friction ridge analysis of developed fingerprints after treatment with various liquid materials on porous surface. (2022) - Nagar, Varad; Tripathi, Krishnanand; Aseri, Vinay; Mavry, Badal; Chopade, Rushikesh L.; Verma, Rohit; Singh, Apoorva; Singh Sankhla, Mahipal; Pritam, Pandit P.; Parihar, Kapil
Abstract: Fingerprints is an important field of research in forensics. Because of its uniqueness and distinctiveness, a fingerprint becomes a person's identity. Experts have devised a number of ways for detecting latent fingerprints on crime scenes. This research study is based on the effects and extent of destruction of latent fingerprints using various lubricants, liquids, and solutions. For this study, 20 samples of various liquids and solutions were collected. Latent fingerprints were taken from 10 individuals on a white paper. These prints were treated with different lubricants, liquids, and solutions by spraying, spilling or submerging the paper. Each sample was dried and the fingerprint was developed with a powder method. This study shows that the type of lubricant or liquid affects the quality of fingerprints developed. In some cases like sanitizer, room fresheners, and other sprays and concentrated phenyl it was noticed that it completely destroyed the latent fingerprints, and in some cases; milk, saliva, tap water, etc results show that it is possible to develop high-quality prints. So, if any paper is recovered from a crime scene in this way then latent prints can be developed from these surfaces. Fingerprints can be obtained from surfaces treated with various liquids, lubricants, especially from milk, tea, coffee, tap water produced high-quality prints which can be analyzed for identification of a person. Future aspects can be so that substances that had destructive effects on the print can be tested for other techniques of development of fingerprints including other factors as well like different porous and non-porous surfaces, environmental effects on these. Because these liquids are a loophole as they are destructive for latent prints.